An investigation of solar photovoltaic systems for potable water and lighting in socially and economically disadvantaged coastal regions - Kazi Meharajul Kabir; M.A. Matin; N. Amin (Energy Nexus)
Bangladesh faces ongoing challenges in providing reliable electricity and clean drinking water, particularly in underprivileged coastal and rural areas. This study presents a low-cost, renewable energy-based system to address these issues, focusing on brackish water purification and nighttime lighting. The coastal zone, rich in solar, wind, and biomass resources, was selected for system design, optimization, and implementation. Simulations show that a solar and biomass hybrid energy system is cost-effective, providing water at $0.021/liter and electricity at $0.14/kWh. However, the high installation costs and need for expert maintenance limit the practicality of biomass for widespread use. Wind energy also proved ineffective in this region. Consequently, a solar photovoltaic (PV) system was identified as the most viable alternative, with costs of $0.022/liter for water and $0.17/kWh for energy. Laboratory testing confirmed that the system's purified water meets international water quality standards, producing potable water at just $0.002/liter, which is much cheaper than bottled water production, which costs $0.009/liter in Bangladesh. This research provides a sustainable solution for Bangladesh's underprivileged communities, contributing to long-term water and energy security.